2002
DOI: 10.1161/01.res.0000036753.50601.e9
|View full text |Cite
|
Sign up to set email alerts
|

Acidification Prevents Endothelial Cell Apoptosis by Axl Activation

Abstract: Abstract-Prior studies have shown that acidification due to hypercarbia protects endothelial cells from serum deprivation-induced apoptosis. However, the mechanism(s) responsible for the antiapoptotic effect of acidification is still unclear. cDNA array screening was performed on human umbilical vein endothelial cells cultured in a bicarbonate medium equilibrated either with 5% CO 2 (pH 7.4) or with 20% CO 2 (pH 7.0). Tyrosine kinase receptor Axl expression was 3.3-fold higher after 6 hours at pH 7.0 compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
(62 reference statements)
4
56
1
2
Order By: Relevance
“…21 Thus, our study demonstrated that hypercapnic acidosis may also affect the VILI by mediating the pathways of ASK1-JNK and p38 MAPK, apoptosis, and inflammatory cytokines in a rat model. 44 …”
Section: Discussionmentioning
confidence: 99%
“…21 Thus, our study demonstrated that hypercapnic acidosis may also affect the VILI by mediating the pathways of ASK1-JNK and p38 MAPK, apoptosis, and inflammatory cytokines in a rat model. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the binding of Gas6 to Axl favors survival of human endothelial cells during acidification (22 ) and protects rat vascular smooth muscle cells from apoptosis (23 ). Moreover, mice deficient for Gas6 receptors present vessel wall abnormalities, including altered histology, increased apoptosis, and cellular degeneration (21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences usually depend on the cell type studied and the concentration used. 4,5,[13][14][15][16][17][18][19][20] It induces migration of smooth muscle cells and inhibits neutrophil adhesion to ECs. 4,20 High concentrations of GAS6 (100-800 ng/mL) inhibit EC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] GAS6 shows the higher affinity for Axl, and its interaction generally triggers antiapoptotic signals, resulting in an augmented cell survival. In some cell types it regulates homotypic and heterotypic adhesion, 4,13 promotes proliferation, 5,14 survival, [15][16][17][18] and motility 19,20 and amplifies the activity of extracellular stimuli. 21,22 Vasculature may be a target of GAS6/Axl axis, being both molecules expressed by endothelial cells (ECs), 4,9 pericytes, 23 and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation